Investigation of milling cutting forces and cutting coefficient for aluminum 6060-T6. (April 2016) - Tsai, M.Y.; Chang, S.Y.; Hung, J.P.; Wang, C.C.
Highlights: Predict the milling cutting force and cutting coefficient for aluminum 6060-T6 successfully. An increase in the feed per tooth increases the cutting force and reduces the cutting coefficient for shearing forces in the tangential direction. The shear angle increased with the feed per tooth and shear stress was close to the actual shear strength of the material. Variation of the feed per tooth and tool diameter did not change the magnitude of the friction angle. Abstract: This paper presents a method to predict the milling cutting force and cutting coefficient for aluminum 6060-T6 which is a general commercial alloy with 170–190 MPa of tensile strength, and is the most commonly used for anodizing and providing extra protection if needed. We introduce two cutting force prediction methods—Altintas and recursive least square (RLS)—and compare their results with experimental values. The influence of the feed per tooth and the tool diameter on the cutting force and cutting coefficient was investigated. After accurately determining the cutting coefficients, the cutting parameters, including the friction angle and shear stress, were estimated using the oblique cutting theory. The forces simulated by the RLS method are in good agreement with the experimentally determined forces. An increase in the feed per tooth is shown to increase the cutting force and reduce the cutting coefficient for shearing forces in the tangential direction. The shear stress in the model is close to the actual shear strength of the material. Graphical abstract: